A psychomotor diagnostic instrument for patients with post-traumatic stress disorder. Issue 1 (2nd January 2018) - van de Kamp, Minke M.; Emck, Claudia; Cuijpers, Pim; Beek, Peter J.
Abstract: Posttraumatic stress disorder (PTSD) is associated with an increased risk of physical disorders as a consequence of chronic stress reactions and adverse lifestyle behaviours. In addition, various other physical signs and symptoms may be present, as well as problems with emotional awareness, such as alexithymia, which may impede verbal information processing. Therefore, a psychomotor diagnostic instrument (PMDI) is developed, based on non-verbal information to contribute to a careful and reliable diagnostic procedure. The PDMI is designed to identify specific goals for body and movement oriented treatments of PTSD. It consists of a manual with an assessment procedure, guidelines for scoring items and for the calculation of cluster scores based on item scores. In this paper, the PMDI and its development are discussed, and illustrated by brief vignettes.